2019
DOI: 10.3390/molecules24152848
|View full text |Cite
|
Sign up to set email alerts
|

Toxicokinetic Study of a Gastroprotective Dose of Capsaicin by HPLC-FLD Method

Abstract: Background: A low dose of capsaicin and its natural homologs and analogs (capsaicinoids) have shown to prevent development of gastric mucosal damage of alcohol and non-steroid anti-inflammatory drugs. Based on this experimental observation, a drug development program has been initiated to develop per os applicable capsaicin containing drugs to eliminate gastrointestinal damage caused by non-steroid anti-inflammatory drugs. Methods: As a part of this program, a sensitive and selective reverse-phase high-perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Formation of phenyl glucuronides and phenyl sulfates are generally considered to be detoxification processes [56]. As our present and previous results [22,23,29,30,34] demonstrate, the formed phenol conjugates can be reexcreted into the gastrointestinal system both by the liver and the small intestine. At the lower PNP concentrations (up to 500 µM), a higher fraction of the absorbed dose is reexcreted into the small intestine in the PNP-G form.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Formation of phenyl glucuronides and phenyl sulfates are generally considered to be detoxification processes [56]. As our present and previous results [22,23,29,30,34] demonstrate, the formed phenol conjugates can be reexcreted into the gastrointestinal system both by the liver and the small intestine. At the lower PNP concentrations (up to 500 µM), a higher fraction of the absorbed dose is reexcreted into the small intestine in the PNP-G form.…”
Section: Discussionsupporting
confidence: 72%
“…The selected doses ensure a lack of acute toxic effects in the investigated organs during the experiments. Furthermore, the therapeutic dose of several phenolic drugs (e.g., estrons [33], capsaicinoids [34]), and the monomer flavonoid content of individual foods [35], fall into the range of our selected concentrations. PNP, having a simple-almost exclusively glucuronide-and sulfate-forming-metabolic profile, seems to be a proper model compound to investigate the relative importance of these two phase II metabolic pathways in the set concentration range.…”
Section: Of 14mentioning
confidence: 99%
“…CAP's slow, sustained release has been correlated with anti-cancer activity [18], a preventive role in gastric cancer [19]. Interestingly, a toxicokinetic study showed that CAP dosed per oral route doesn't reach circulation; however, it prevents gastric damage and works like NSAID [41], which may become a suitable candidate for therapeutic use. It was also observed in an exploratory study on human subjects that ingestion of red chilli strongly affects gastric accommodation, which could be helpful in gastroesophageal reflux disease patients [42].…”
Section: 2mentioning
confidence: 99%
“…Several analytical techniques have been applied for the analysis of capsaicinoids, including gas chromatography [5] and liquid chromatography (LC), which has been by far the most widely preferred [6][7][8][9][10][11][12][13][14][15][16][17][18]. LC methods tend to use UV absorption spectrophotometry [6], fluorescence detection (FLD) [7][8][9], and mass spectrometry (MS) [10][11][12][13][14][15][16][17][18] as detection systems.…”
Section: Introductionmentioning
confidence: 99%